A Monolithically Processed Rectifying Pixel for High‐Resolution Organic Imagers. (24th March 2018) - Zalar, Peter; Matsuhisa, Naoji; Suzuki, Toshiki; Enomoto, Shintaro; Koizumi, Mari; Yokota, Tomoyuki; Sekino, Masaki; Someya, Takao
Abstract: Integration of switching elements with sensing elements in a sensor array is a crucial platform for "sensing surfaces". Of particular interest are imaging surfaces, especially for applications such as X‐ray imaging or fingerprint sensors. Since a photodiode loses its rectifying properties upon illumination, it requires a switching element so that meaningful data can be obtained from each individual pixel. To solve this problem, we have developed a monolithically processed rectifying pixel which enables high resolution organic imaging devices. Our organic imager has pixel pitches as small as 50 µm, with resolutions of up to 262 ppi. The pixel's individual light intensity dependent and spectral response characteristics were characterized as a function of voltage. As a total imaging system, the imageable resolution was also determined. The applicability of the imager was validated by steady state images, but also by real‐time video acquisition and by spatial photoplethysmography (PPG) measurements on the ball of a human foot. Abstract : An organic imager based on a monolithically fabricated rectifying pixel is demonstrated enabling high‐resolution imaging. Since photodiodes lose their rectification under illumination, imaging in a passive matrix is nearly impossible due to crosstalk. Using a rectifying diode in series with a photodiode, pixels can "rectify" in the illumination state, circumventing the need of using transistors.